2018
DOI: 10.1111/jns.12288
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ opioid peptide‐receptor expression in pachyonychia congenita

Abstract: Nociceptin/orphanin FQ opioid peptide (NOP)‐receptor (NOP‐R) is a member of the opioid receptor family. NOP‐R activation has demonstrated analgesic effects in preclinical pain models without the addiction risks associated with other opiate targets. Pachyonychia congenita (PC) is a palmoplantar keratoderma characterized by neuropathic pain in affected skin. A cohort of KRT6A gene mutation PC patients with no other explanation for their neuropathic pain offered a unique opportunity to assess potential of NOP‐R a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Many treatments for PC, such as Botox injections [60, 61], focus on pain management. Although some research has focused on treatment of the underlying cause, such as reducing expression of keratin alleles [62, 63], success has only been reported in small group case reports.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Many treatments for PC, such as Botox injections [60, 61], focus on pain management. Although some research has focused on treatment of the underlying cause, such as reducing expression of keratin alleles [62, 63], success has only been reported in small group case reports.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In patients with NP due to pachyonychia congenita, overexpression of NOR on epidermal keratinocytes and epidermal and dermal nerve fibers has been demonstrated [284]. Recently, NOR has been identified on human blood granulocytes as well [285].…”
Section: Treatments Acting On Peripheral Opioid Receptorsmentioning
confidence: 99%
“…The preclinical studies showed stimulation of keratinocytes alone to be sufficient to induce neuronal hyperexcitability and pain behaviour in animals [87,88]. According to preclinical data, keratinocytes express several receptors and ion channels, playing role in nociception, such as Nav (Nav 1.1,1.2, 1.5,1.6,1.7,1.8), TRP (TRPV1-4), neurokinin 1 receptor (NK1-receptor, NK1R), TLR, interleukin receptors, α1-AR, endothelin1 receptors (ET1), calcitonin receptor-like receptor (CRLR), CB receptors, OR, NOP (nociceptin-orphanin opioid peptide) receptors (NOP-R), VGCC, NMDAR, and GABAR to mention a few [89][90][91][92][93][94][95][96]. The role of keratinocyte receptors and their overexpression in nociception has been confirmed in clinical observations.…”
Section: 4 the Role Of Skin Cells In Peripheral Mechanisms Of Npmentioning
confidence: 99%